Abrupt cooling events during the Early Holocene and their potential impact on the environment and human behaviour along the southern North Sea basin (NW Europe). (10th July 2017) - Crombé, Philippe
ABSTRACT: In this paper the potential impact of the 9.3k cal a BP cooling event on the environment and human occupation in the Rhine–Meuse–Scheldt region of NW Europe is investigated. Although various environmental (decreased fluvial activity, increased wildfires and changing vegetation) and cultural changes (lithic technology, raw material circulation, decreasing site density) can be identified in the (late) Boreal, a serious problem of equifinality remains. Lacking a high‐resolution chronology for these events, it is still difficult to separate the impact of gradual from punctuated climatic changes. However, at present it seems that (some) environmental and cultural changes were already ongoing before the 9.3k cal a BP event but were accelerated by the latter. To gain a better understanding of these processes, it is necessary to take a holistic, multidisciplinary approach towards the Early Holocene in the southern North Sea basin.